2011
DOI: 10.4021/jocmr542w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Comparison of Conventional Testicular Sperm Extraction and Microdissection Techniques for Non-Obstructive Azoospermia

Abstract: BackgroundWe compared the efficacy of microdissection testicular sperm extraction (microdissection TESE) and conventional TESE in patients with non-obstructive azoospermia (NOA) and related the positive sperm recovery to certain variables: follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels, testicular volume and histology.MethodsSperm retrieval rates (SRR) in patients with NOA who underwent microdissection TESE (n = 65) or conventional TESE (n = 68) were compared and related to the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
68
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 22 publications
(29 reference statements)
2
68
0
2
Order By: Relevance
“…16.7 (n = 24) 37.5 (n = 8) 6.3 (n = 16) 44.6 (n = 74)* 75 (n = 12) 33.9 (n = 56)* Tsujimura et al, 2002 35.1 (n = 37) 76.9 (n = 13) 0 (n = 1) 13 (n = 23) 42.9 (n = 56) 100 (n = 12) 75 (n = 4) 22.5 (n = 40) Ramasamy et al, 2005 32 (n = 83) 50 (n = 14) 20 (n = 10) 29 (n = 24) 57 (n = 460)* 81 (n = 73)* 44 (n = 62) 41 (n = 237) Ghalayini et al, 2011 38.2 (n = 68) 84 (n = 25) 27.3 (n = 11) 6.2 (n = 32) 56.9 (n = 65)* 92.9 (n = 28) 36.4 (n = 11) 26.9 (n = 26)* *Statistically significant (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16.7 (n = 24) 37.5 (n = 8) 6.3 (n = 16) 44.6 (n = 74)* 75 (n = 12) 33.9 (n = 56)* Tsujimura et al, 2002 35.1 (n = 37) 76.9 (n = 13) 0 (n = 1) 13 (n = 23) 42.9 (n = 56) 100 (n = 12) 75 (n = 4) 22.5 (n = 40) Ramasamy et al, 2005 32 (n = 83) 50 (n = 14) 20 (n = 10) 29 (n = 24) 57 (n = 460)* 81 (n = 73)* 44 (n = 62) 41 (n = 237) Ghalayini et al, 2011 38.2 (n = 68) 84 (n = 25) 27.3 (n = 11) 6.2 (n = 32) 56.9 (n = 65)* 92.9 (n = 28) 36.4 (n = 11) 26.9 (n = 26)* *Statistically significant (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, four studies (Okada et al, 2002;Tsujimura et al, 2002;Ramasamy et al, 2005;Ghalayini et al, 2011) directly compared SRRs between c-TESE and micro-TESE, relating to histopathology findings (SCOS and MA). The hypospermatogenesis was studied in three out of the four manuscripts (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this analysis may not have reflected histopathologic status of the whole testis of the infertile men. Consistently, it has been shown that multiple biopsy samples from different parts of the testis resulted in sperm retrieval in patients with azoospermic testis and even in the patients with SCO in certain cases [40,41]. As a result, since obtaining testicular biopsy materials from one part of human testis cannot represent histopathologic status of the whole testis, it may affect the accuracy of findings.…”
Section: Discussionmentioning
confidence: 98%
“…However, in a number of studies on mTESE a biopsy for histology is only obtained during the surgical sperm retrieval thereby excluding the prognostic value of histopathological diagnosis (Tsujimura et al, 2002;Ramasamy et al, 2005;Turunc et al, 2010;Ghalayini et al, 2011). For example, in a study by Ramasamy et al (2005) histopathological diagnosis was known from prior biopsies in some patients, whereas the other patients had a biopsy taken during the surgical sperm retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…As a result and because of the relatively high SRR and low reported complication rates (Schlegel, 1999;Amer et al, 2000;Okada et al, 2002;Tsujimura et al, 2002;Ramasamy et al, 2005;Turunc et al, 2010;Ghalayini et al, 2011) many centers use mTESE as the first choice of retrieving spermatozoa in NOA. However, this global approach does not allow for individualized treatment based on the patients needs.…”
Section: Discussionmentioning
confidence: 99%